The influence of broadband regulation in EU on the development of the regulated technology - Mihevc, Andrej (Organizacija (Kranj), 2011)
The aim of the article is to answer the question if the level of intensity of `ex ante` regulation (also `regulation`) imposed by NRA (national regulatory Authority or regulators) influence on the development of incumbent DSL technology against other Access technologies. There are several approaches which support the basic idea of regulation, that Ćex anteĆ regulation promotes the competition. The approaches must be also based on the size of themarket. In the internet world there are different access technologies. OpenAccess is crucial for the development of competition. Regulators have to ensure, that also new entrants can reach end users through the facilities of the incumbent operator. Based on the approach of three criteria, European Commission defines two wholesale relevant access markets both based on DSL technology (`bitstream` access and unbundled local loop) susceptible to sector specific `ex ante` regulation. In the last stage also optical access isincluded on the relevant markets. Other technologies are still not equivalent to incumbent DSL technology according to the opinion of the commission. The intensity of regulation influences on the competition conditions. It influences on the level where and at which point of the investment ladder entrants will enter the market through wholesale inputs or through building its own infrastructure.
Keywords: European Union; Evropska unija; telecommunication; telekomunikacije; telekomunikacijska omrežja; širokopasovna telekomunikacijska omrežja; konkurenca; regulacija